Pengaruh Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA di Kelas III SDN 1 Ayong - Potabuga, Fitria K.; Rawis, Joulanda A. M.; Komedien, Brianne E. Jo. (Peneliti.net, 2023)
The aim of this research is to determine the improvement in student learning outcomes through the Contextual Teaching and Learning (CTL) approach to the material